Development of adjuvanted recombinant zoster vaccine and its implications for shingles prevention. (3rd July 2018) - Lecrenier, Nicolas; Beukelaers, Pierre; Colindres, Romulo; Curran, Desmond; De Kesel, Carine; De Saegher, Jean-Philippe; Didierlaurent, Arnaud M; Ledent, Edouard Y; Mols, Johann F; Mrkvan, Tomas; Normand-Bayle, Marie; Oostvogels, Lidia; et al.
ABSTRACT: Introduction : GSK has developed a two-dose adjuvanted recombinant zoster vaccine ( Shingrix, RZV) to protect people aged ≥50 years (50+) against herpes zoster (HZ) and its complications. RZV showed >90% efficacy against HZ, sustained over 4 years of follow-up, in all studied age groups. Areas covered : This article reviews the scientific rationale underlying the design of RZV; the clinical evidence demonstrating immunogenicity, safety, and efficacy in persons 50+; and the public health implications and cost-effectiveness. Expert commentary : A decline in varicella zoster virus (VZV) immunity is associated with increased risk of HZ in adults 50+ and immunocompromised individuals. RZV was designed to restore levels of anti-VZV cellular and humoral immunity to prevent VZV reactivation. RZV includes the recombinant gE glycoprotein antigen, and Adjuvant System AS01B which promotes cellular and antibody responses. In two Phase III studies in subjects aged 50+ and 70+ years, RZV efficacy against HZ compared to placebo was >90% and ≥89% against post-herpetic neuralgia (PHN). RZV is expected to dramatically impact HZ morbidity including its complications, and associated health-care costs. In the US population aged 50+ years, vaccination with RZV can be cost-effective compared to no vaccination and cost-saving compared to the currently available live-attenuated HZ vaccine ( Zostavax, Merck ). Abstract :